Literature Review: Factors Affecting The Performance Accountability Report of Government Agencies (LAKIP) Local Government in Indonesia - Idel Eprianto (Profesional Muda Cendekia Publishing, 2023)
This article is a literature review the factors that affect the performance accountability report of government agencies (LAKIP) of local governments in Indonesia which is the dependent variable. While the independent variable is compliance with legislation, competence of human resources, clarity of budget goals. The hypothesis that is built is to examine the influence between variables so that it can be used in further research. The results of the literature review show the influence of the variable compliance with regulations, human resources competency and clarity of budget goal to LAKIP local governments in Indonesia.